Prevalence of Overweight and Obesity in Children and Adolescents from the Age Range of 2 to 19 Years Old in Brazil - Janaina R. Niehues; Ana Inês Gonzales; Robson R. Lemos; Poliana Penasso Bezerra; Patrícia Haas (International Journal of Pediatrics)
Introduction. Infant juvenile obesity is currently a worldwide public health problem and it is increasing at alarming rate in the Brazilian population, showing its relevance in terms of public health. Objectives. Determine the prevalence of overweight and obesity in children and adolescents between 2 and 19 years old in different regions of Brazil. Methods. The following electronic databases were searched (from September through November 2013): Medline (PubMed), LILACS, and SciELO, using the descriptors and Boolean operators (obesity) and (overweight) and (child) and (prevalence) and (Brazil). Prospective and/or cross-sectional designs studies were found regarding the prevalence of overweight and obese children and adolescents in the five regions of Brazil. Results. A total of 191 scientific articles were found of which 17 met all inclusion criteria. A higher prevalence of overweight was found in the south (25.7%) and north (28.8%) of the country, and obesity in the southeast (15.4%) and south (10.4%). Conclusions. The scope of the studies was mostly based on municipal coverage, which resulted in limitations for conclusive analysis, showing the need for further studies of prevalence at the national level, with emphasis on public health in obese children and adolescents throughout the Brazilian territory.